Do disparities exist between national food group recommendations and the dietary intakes of contemporary young adults?. Issue 5 (24th June 2021) - Taylor, Rachael M.; Haslam, Rebecca L.; Truby, Helen; Attia, John; Hutchesson, Melinda J.; Burrows, Tracy; Callister, Robin; Hides, Leanne; Bonevski, Billie; Kirkpatrick, Sharon; Ashton, Lee; Collins, Clare E.
Abstract: Aim: The aim of this study was to compare food and nutrient intakes of young Australian adults (18‐24 years) to national recommendations as per the Australian Guide to Healthy Eating and Nutrient Reference Values. Methods: Dietary intake of 18 to 24 year olds (n = 1005) participating in the Advice, Ideas, and Motivation for My Eating (Aim4Me) study was self‐reported using the 120‐item Australian Eating Survey Food Frequency Questionnaire. Median daily servings of Australian Guide to Healthy Eating food groups, macronutrients and micronutrients were compared to recommendations in the Australian Guide to Healthy Eating and Nutrient Reference Values using t‐tests or Kruskal‐Wallis tests ( P < .05). Results: None of the young adults met all Australian Guide to Healthy Eating recommendations. The highest adherence [% meeting recommendations, median (IQR)] was for meat/alternatives [38%, 2.1(1.8)] and fruit [32%, 1.5(1.6)], with <25% meeting remaining food‐group recommendations. The majority (76%) exceeded recommendations for the consumption of discretionary foods [4.0(3.3) vs 0‐3 serves] and 81% had excessive saturated fat intakes. Young adults who met all key Nutrient Reference Values (dietary fibre, folate, iodine, iron, calcium and zinc) (18%) consumed a higher number of serves of all food groups, including discretionary foods. Conclusions: Dietary intakes of contemporary young adults do not align with Australian Guide to Healthy Eating targets, while meeting Nutrient Reference Values is achieved by a higher consumption of all food groups, including discretionary foods. Strategies to increase consumption of nutrient‐dense foods in young adults to achieve the Nutrient Reference Values are warranted.